Adopting open source software : a practical guide. - Fitzgerald, Brian, 1959-; Kesan, Jay P., ....-; Russo, Barbara, ....- (Cambridge : MIT, 2011)
Government agencies and public organizations often consider adopting open source software (OSS) for reasons of transparency, cost, citizen access, and greater efficiency in communication and delivering services. Adopting Open Source Software offers five richly detailed real-world case studies of OSS adoption by public organizations. The authors analyze the cases and develop an overarching, conceptual framework to clarify the various enablers and inhibitors of OSS adoption in the public sector. The book provides a useful resource for policymakers, practitioners, and academics.The five cases of OSS adoption include a hospital in Ireland; an IT consortium serving all the municipalities of the province of Bozen-Bolzano, Italy; schools and public offices in the Extremadura region of Spain; the Massachusetts state government's open standards policy in the United States; and the ICT department of the Italian Chamber of Deputies. The book provides a comparative analysis of these cases around the issues of motivation, strategies, technologies, economic and social aspects, and the implications for theory and practice.